1995
DOI: 10.1148/radiology.195.3.7753991
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acquired cystic kidney disease and tumors in native kidneys of renal transplant recipients: a prospective US study.

Abstract: The frequency of ACKD increases with the duration of hemodialysis. The risk for the development of ACKD is increased in men and older patients. The malignant potential of ACKD persists after renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
3
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 0 publications
3
49
3
4
Order By: Relevance
“…The median time from transplant to development of any renal cancer was 4.5 years for RCC and 2.1 years for TCC. Although other studies have demonstrated that a higher proportion of tumors occur in the native kidney, 12,13 our results demonstrate that the median times for development of both RCC and TCC in the native kidney were much shorter than in the allograft. In contrast to our findings, other studies have shown a longer median time of 3.9 to 7.4 years for development of RCC and 4.4 to 4.8 years for TCC after renal transplant.…”
Section: Discussioncontrasting
confidence: 74%
“…The median time from transplant to development of any renal cancer was 4.5 years for RCC and 2.1 years for TCC. Although other studies have demonstrated that a higher proportion of tumors occur in the native kidney, 12,13 our results demonstrate that the median times for development of both RCC and TCC in the native kidney were much shorter than in the allograft. In contrast to our findings, other studies have shown a longer median time of 3.9 to 7.4 years for development of RCC and 4.4 to 4.8 years for TCC after renal transplant.…”
Section: Discussioncontrasting
confidence: 74%
“…Schwarz et al (9) reported a relatively high prevalence of RCC in kidney transplant patients with ACKD. Therefore, they concluded that ACKD was a risk factor for RCC among kidney transplant recipients and screening such as ultrasound should be performed for RCC in such patients, which consistent with study of Heinz-Peer et al (10) reported a high prevalence of RCC in patients undergoing kidney transplantation.…”
Section: Implication For Health Policy/practice/research/medical Educsupporting
confidence: 68%
“…In this study, in all but one patient kidney neoplasms were detected over 5 years after renal transplantation, with tumor sizes ranging from 16 to 35 mm. Assuming a growth rate of renal carcinomas in allotransplanted patients of 0.5-1 .O cm/year, these tumors had to originate after kidney transplantation [4]. It has been shown that none of the patients, neither kidney recipients nor any from the control group, had local disease recurrence or distant metastasis in a median of almost 3 years after radical treatment.…”
Section: Discussionmentioning
confidence: 99%